Modification of free-volume defects in the GaS2–Ga2S3– CsCl glasses - Klym, H.; Calvez, L.; Popov, Anatoli I. (Springer, 2023)
Modification of free-volume positron trapping defects in the GaS2–Ga2S3–CsCl chalcogenide glasses was studied using positron annihilation lifetime spectroscopy and Doppler broadening of annihilation radiation methods. It is shown that the addition of CsCl to the main glass matrix leads to agglomeration of internal free-volume defects, which are di- or tri-atomic vacancies. However, an excessive amount of CsCl component causes a decrease in the size and content of these defects in the internal structure of the glass against the background of water adsorption in nanovoids with a radius of 0.3 nm. The obtained results are confirmed by normal and abnormal trends in the correlation of the S parameter, which characterizes the annihilation of positrons with low-momentum valence electrons and the W parameter, which corresponds to the annihilation of positrons with high-momentum core electrons. --//-- This is an open access article H. Klym*, L. Calvez, A.I. Popov; Modification of free-volume defects in the GaS2–Ga2S3–CsCl glasses; J. Mater. Sci.: Mater. Electron., 2023, 34, 1104 (pp. 1-9); DOI: 10.1007/s10854-023-10431-9; https://link.springer.com/article/10.1007/s10854-023-10431-9 published under the CC BY licence.
HK would like to thanks Ministry of Education and Science of Ukraine (Project No. 0122U000807) as well as Dr. A. Ingram for assistance in PAL and DRAL experiments and Prof. O. Spotyuk for discussions. In addition, the research of AIP was partly supported by the RADON project (GA 872494) within the H2020-MSCA-RISE-2019 call and COST Action CA20129 “Multiscale Irradiation and Chemistry Driven Processes and Related Technologies” (MultIChem). AIP also thanks to the Institute of Solid-State Physics, University of Latvia. ISSP UL as the Center of Excellence is supported through the Framework Program for European universities, Union Horizon 2020, H2020-WIDESPREAD-01-2016-2017-TeamingPhase2, under Grant Agreement No. 739508, CAMART2 project.
Keywords: Research Subject Categories::NATURAL SCIENCES; Research Subject Categories::NATURAL SCIENCES::Physics